Php5 And Mysql Bible - Converse, Tim (Wiley Publishing, 2011)
This comprehensive tutorial and reference covers all the basics of PHP 5, a popular open source Web scripting language, and MySQL 4.012, the most popular open source database engine Explores why users need PHP and MySQL, how to get started, how to add PHP to HTML, and how to connect HTML Web pages to MySQL Offers an extensive tutorial for developing applications with PHP and MySQL Includes coverage of how to install, administer, and design MySQL databases independently of PHP; exception and error handling; debugging techniques; PostgreSQL database system; and PEAR database functions The authors provide unique case studies of how and where to use PHP drawn from their own extensive Web experience